Genomic Analysis of an Obesity Paradox: A Microarray Study of the Aortas of Morbidly Obese Decedents With Mild and Severe Atherosclerosis. Issue 1 (March 2019) - Brodsky, Sergey V.; Ganju, Ramesh; Mishra, Sanjay; Ivanov, Iouri; Fadda, Paolo; Wang, Huabao; Barth, Rolf F.
Abstract : Background: Atherosclerosis of the aorta and coronary arteries is still one of the major causes of death. We recently reported obesity paradox between body mass index and atherosclerosis of the aortas (AA) in morbidly obese decedent patients. The cause of this obesity paradox is unknown. The aim of the present study was to carry out genomic microarray analysis to determine gene expression profiles in the aortas of morbidly obese decedents with either mild or severe atherosclerosis of the aorta. Methods: Microarray studies using Affymetrix GeneChips Clariom D Human array chips were performed on the aortas obtained from 6 morbidly obese decedents, 3 of whom had minimal AA and 3 who had severe disease. Results: Group 1 (severe AA) and group 2 (mild AA) included 3 patients each. The patients were matched by age and body mass index. There were significant ( P <0.005) differences in the expressions of 1067 genes between groups 1 and 2, including 602 upregulated and 465 downregulated genes. Conclusions: Our data show significantly different gene signatures between morbidly obese decedents who have mild or severe AA, suggesting that genetic factors may be important contributors to the obesity paradox as it relates to aortic atherosclerosis. Further studies are warranted to define differences in protein expression in the aortas of these 2 groups to further elucidate the cause of this obesity paradox.